Mapping the Digital Transformation of Microfinance Research: A Bibliometric Analysis - Chaity, Naznin Sultana; Rahaman, Mahabubur (European Scientific Journal, ESJ, 2026)
Digital transformation is fundamentally reshaping microfinance institutions worldwide, yet the cumulative evidence base on its effects remains fragmented across disciplinary and methodological boundaries. This study presents a bibliometric analysis of the multidimensional impact of digital transformation on microfinance research. Primary data were drawn from journal articles published between 2018 and 2024. An initial pool of 1,000 documents was retrieved, of which 562 articles were retained for analysis after applying predefined inclusion and exclusion criteria. Keyword co-occurrence analysis and descriptive statistics were used in VOSviewer to map the field’s intellectual structure. The analysis identifies seven thematic clusters, revealing that institutional capacity, regulatory quality, digital infrastructure, and sociocultural context function as critical moderating conditions that determine whether digital transformation yields inclusive or exclusionary outcomes. The findings further indicate that the COVID-19 pandemic significantly accelerated digital adoption among microfinance institutions. Collectively, this bibliometric synthesis offers a replicable analytical framework to guide future evidence-building in digital microfinance research, while highlighting critical avenues for theoretical and empirical advancement in the field.